Organizational performance through the donation and collection of interorganizational knowledge. Issue 1 (8th February 2016) - Nodari, Felipe; Oliveira, Mirian; Maçada, Antonio Carlos Gastaud
Abstract : Purpose: – This paper aims to provide empirical evidence to support the relationship between interorganizational knowledge sharing, absorptive capacity and organizational performance, and proposes that interorganizational knowledge sharing is composed of two processes: knowledge donation and collection. Design/methodology/approach: – A quantitative methodology is adopted to examine the proposed relationship between interorganizational knowledge sharing, absorptive capacity and organizational performance. The study uses survey data from 269 companies in Brazil. Structural equation modeling is applied to test the stated hypotheses and the model. Findings: – The empirical findings indicate that interorganizational knowledge sharing is composed of the donation and collection of knowledge. Interorganizational knowledge collection is found to have a positive effect on interorganizational knowledge donation, while collection is found to have a positive effect, mediated by absorptive capacity, on organizational performance. Research limitations/implications: – One limitation of this research was the predominant participation of smaller companies. Another is that the data were only collected from Brazilian companies. Moreover, an instrument to measure these constructs was proposed and validated to enable future research to be conducted into the process of interorganizational knowledge sharing and its components: knowledge donation and knowledge collection. Practical implications: – Managers can enhance organizational performance by developing both the donation and collection of knowledge. Knowledge donation is particularly important because, in addition to its impact on absorptive capacity and organizational performance, it contributes to the development of knowledge collection, which is also indirectly related to performance. Originality value: – The donation and collection of knowledge were validated as components of the interorganizational knowledge-sharing process, and the relationship between these processes and organizational performance is mediated by the absorptive capacity of the organization.